Model Regresi Data Mining Motivasi Belajar Pengaruhnya Terhadap Tingkat Kedisiplinan Mahasiswa - Hindayati Mustafidah (JUITA : Jurnal Informatika, 2010)
Data Mining as one of the development of Artificial Intelligence area has been developed primarily in the areas of business. In this research, data mining process in the case of the influence of motivation on the level of student discipline in following the lectures in college, assuming that the higher thestudents' motivation will be spurred to become more disciplined in following college activities. The method used was the two models are linear and quadratic regression. From the analysis, obtained by error (mse) of 8.13% for the linear regression model and errors (mse) of 8.15% for the quadratic regression model. Based on the results of the analysis, the conclusion is moreappropriate linear regression model applied in this case because it gives a smaller error than the quadratic regression model.